2015
DOI: 10.1159/000370237
|View full text |Cite
|
Sign up to set email alerts
|

Newborn Infants Detect Cues of Concurrent Sound Segregation

Abstract: Separating concurrent sounds is fundamental for a veridical perception of one's auditory surroundings. Sound components that are harmonically related and start at the same time are usually grouped into a common perceptual object, whereas components that are not in harmonic relation or have different onset times are more likely to be perceived in terms of separate objects. Here we tested whether neonates are able to pick up the cues supporting this sound organization principle. We presented newborn infants with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(21 citation statements)
references
References 48 publications
0
21
0
Order By: Relevance
“…Thus, the P400 amplitude is linked directly to behavioral performance in two different ways, whereas the ORN amplitude does not show a similar correspondence to behavior. Furthermore, while ORN is elicited in passive situations (similarly to the brain electric activity observed by O’Sullivan et al, 2015) and has been observed in newborns and 6-month-old infants (Bendixen et. al, 2015; Folland, Butler, Smith, & Trainor, 2012), P400 is only elicited when listeners are instructed to report whether they heard one or two concurrent objects (e.g., Alain et al2001; McDonald and Alain 2005; Kocsis et al, 2014).…”
Section: Discussionmentioning
confidence: 60%
“…Thus, the P400 amplitude is linked directly to behavioral performance in two different ways, whereas the ORN amplitude does not show a similar correspondence to behavior. Furthermore, while ORN is elicited in passive situations (similarly to the brain electric activity observed by O’Sullivan et al, 2015) and has been observed in newborns and 6-month-old infants (Bendixen et. al, 2015; Folland, Butler, Smith, & Trainor, 2012), P400 is only elicited when listeners are instructed to report whether they heard one or two concurrent objects (e.g., Alain et al2001; McDonald and Alain 2005; Kocsis et al, 2014).…”
Section: Discussionmentioning
confidence: 60%
“…However, the ability to distinguish melodic consonance/dissonance appears to have genetic roots—just as its harmonic counterpart—according to the EEG measurements during newborn infants' sleep (Stefanics et al, 2009 ). The newborns can segregate concurrent tones into separate audio streams by detecting inharmonic relations between the co-occurring sounds (Bendixen et al, 2015 ).…”
Section: Toward Taxonomy Of Melodic Intervalsmentioning
confidence: 99%
“…Unlike vision, hearing makes environmental information readily available for the brain right from birth. Neonates are found to have all the main auditory functionality that characterizes adults' hearing in place (Bendixen et al, 2015 ). This includes discrimination between melodic intervals (Stefanics et al, 2009 ).…”
Section: Summary: Pitch Organization As a General Organizational Schementioning
confidence: 99%
“…However, whether infants are able to use auditory cues to group and separate frequency components is less clear. The results of several studies suggest that infants are able to use frequency separation (Demany, 1982;Winkler et al, 2003), harmonicity (Bendixen et al, 2015;Folland et al, 2015;Folland et al, 2012), and spatial location cues (Nozza, 1988). However, the results of these studies fail to provide a cohesive account of the development of sound segregation for several reasons.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the auditory cue is rarely systematically varied in developmental studies. Instead, infants are presented with a cue that is large enough to allow adults to easily segregate the sounds involved (e.g., Bendixen et al, 2015;Winkler et al, 2003). Although this approach demonstrates that infants can use a specific cue, it does not provide a way to assess how efficiently infants use that auditory cue relative to adults.…”
Section: Introductionmentioning
confidence: 99%